Transformation of Atmospheric CO2 Catalyzed by Protic Ionic Liquids: Efficient Synthesis of 2‐Oxazolidinones1. Issue 18 (3rd March 2015) - Hu, Jiayin; Ma, Jun; Zhu, Qinggong; Zhang, Zhaofu; Wu, Congyi; Han, Buxing
Abstract Protic ionic liquids (PILs), such as 1, 8‐diazabicyclo[5.4.0]‐7‐undecenium 2‐methylimidazolide [DBUH][MIm], can catalyze the reaction of atmospheric CO2 with a broad range of propargylic amines to form the corresponding 2‐oxazolidinones. The products are formed in high yields under mild, metal‐free conditions. The cheaper and greener PILs can be easily recycled and reused at least five times without a decrease in the catalytic activity and selectivity. A reaction mechanism was proposed on the basis of a detailed DFT study which indicates that both the cation and anion of the PIL play key synergistic roles in accelerating the reaction.